LITERASI DINI MELALUI TEKNIK BERNYANYI - Dinar Nur Inten; Andalusia Neneng Permatasari; Dewi Mulyani (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstract: Singing is one of the emergent literacy learning techniques that can be used by early childhood teachers. By technique of singing, early childhood teachers can establish all of emergent literacy activities based on children’s needs and interests. Through Literacy with singing techniques, early childhood teachers can introduce reading and writing unnoticed to the children because the children felt he wasn’t learning but singing and playing. Therefore, singing technique could be an alternative emergent literacy teaching technique for early childhood.Keywords; Emergent Literacy, Technique Of Singing, Early Childhood